Removal of Arsenic from Aqueous Solution by Fe(III)-Impregnated Sorbent Prepared from Sugarcane Bagasse - Liang, Meina; Zhu, Yinian; Wang, Dunqiu; Zhang, Hua; Zhu, Zongqiang; Chen, Zhihong (Asian Journal of Chemistry, 2013)
An Fe(III)-impregnated adsorbent was prepared from sugarcane bagasse and FeCl3 solution via carbonization/activation in a muffle furnace at 500 ºC for 4 h. The sorption removal of arsenic from aqueous solution by the prepared sorbent was then studied in a batch system. In order to investigate the mechanism of sorption, this paper employs the four different kinetic models to fit to the experimental data. The studies showed that within 0.5 h this sorbent was able to remove 96.96, 95.99 and 94.60 % of arsenic from water containing an initial arsenic concentration of 1, 2 and 4 mg/L, respectively. At initial pH from 3 to 12, the arsenic concentration of treated solution was lesser than 5 μg/L at the initial arsenic concentration of 2 mg/L, it was far below the U.S. EPA standard (10 μg/L). The pseudo-second-order kinetic model generated the best fit to the experimental data with regression coefficients R2 = 1.0000.